2012
DOI: 10.1093/nar/gks655
|View full text |Cite
|
Sign up to set email alerts
|

Poly(A) binding protein nuclear 1 levels affect alternative polyadenylation

Abstract: The choice for a polyadenylation site determines the length of the 3′-untranslated region (3′-UTRs) of an mRNA. Inclusion or exclusion of regulatory sequences in the 3′-UTR may ultimately affect gene expression levels. Poly(A) binding protein nuclear 1 (PABPN1) is involved in polyadenylation of pre-mRNAs. An alanine repeat expansion in PABPN1 (exp-PABPN1) causes oculopharyngeal muscular dystrophy (OPMD). We hypothesized that previously observed disturbed gene expression patterns in OPMD muscles may have been t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
186
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 150 publications
(217 citation statements)
references
References 53 publications
15
186
2
1
Order By: Relevance
“…Recent studies suggested that the mutant PABPN1 protein, called trePABPN1, acts as a dominantnegative factor by trapping the wild-type protein in insoluble nuclear inclusion bodies . Global mapping of RNA polyadenylation in trePABPN1-expressing cells and using an OPMD mouse model revealed a systematic shift of the APA profile toward proximal PASs, similar to the effect of PABPN1 loss-of-function (de Klerk et al 2012;Jenal et al 2012). It will be important to understand how the observed aberrant APA pattern contributes to the pathology of OPMD and why only certain muscle cells are affected by this defect.…”
Section: Global Analyses Of Apa Regulation In Human Diseasesmentioning
confidence: 76%
See 1 more Smart Citation
“…Recent studies suggested that the mutant PABPN1 protein, called trePABPN1, acts as a dominantnegative factor by trapping the wild-type protein in insoluble nuclear inclusion bodies . Global mapping of RNA polyadenylation in trePABPN1-expressing cells and using an OPMD mouse model revealed a systematic shift of the APA profile toward proximal PASs, similar to the effect of PABPN1 loss-of-function (de Klerk et al 2012;Jenal et al 2012). It will be important to understand how the observed aberrant APA pattern contributes to the pathology of OPMD and why only certain muscle cells are affected by this defect.…”
Section: Global Analyses Of Apa Regulation In Human Diseasesmentioning
confidence: 76%
“…Such APA changes are accompanied by the up-regulation of many microRNA target mRNAs, suggesting coupling between APA-and microRNA-mediated gene regulation (Park et al 2011). 39 UTR shortening was also observed in oculopharyngeal muscular dystrophy (OPMD) (de Klerk et al 2012;Jenal et al 2012). This neuromuscular disease is caused by ''prion''-like mutant PABPN1 proteins that have an expanded polyalanine region due to a trinucleotide (GCN) expansion in the PABPN1 gene.…”
Section: Global Analyses Of Apa Regulation In Human Diseasesmentioning
confidence: 99%
“…Experiments in Schizosaccharomyces pombe and mammalian cells (Lemay et al , 2010 ;Lemieux et al , 2011 ;Beaulieu et al , 2012 ) suggest that PABPN1 has an additional function in promoting the activity of the exosome, a protein complex with 3 ′ exonuclease activity involved in many RNA decay and processing reactions both in the nucleus and the cytoplasm. A role of PABPN1 in alternative polyadenylation has also recently been described (de Klerk et al , 2012 ;Jenal et al , 2012 ).…”
Section: The Nuclear Poly(a)-binding Proteinmentioning
confidence: 88%
“…Immortalized mouse myoblasts, C2C12, were propagated as described in de Klerk et al 23. Immortalized human myoblasts, 7304.1, were cultured according to Anvar et al 24.…”
Section: Methodsmentioning
confidence: 99%